2016
DOI: 10.3390/molecules21070948
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Degradation of Caffeoylquinic Acids under Different Storage Conditions Studied by High-Performance Liquid Chromatography with Photo Diode Array Detection and High-Performance Liquid Chromatography with Electrospray Ionization Collision-Induced Dissociation Tandem Mass Spectrometry

Abstract: Caffeoylquinic acids (CQAs) are main constituents in many herbal medicines with various biological and pharmacological effects. However, CQAs will degrade or isomerize when affected by temperature, pH, light, etc. In this study, high-performance liquid chromatography with photodiode array detection (HPLC-PDA) and high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) was utilized to study the stability and degradation of CQAs (three mono-acyl CQAs and four di-acyl CQAs) under various ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 19 publications
(25 reference statements)
8
59
1
Order By: Relevance
“…According to Deshpande et al (2014) under the aqueous basic conditions the intramolecular acyl migration in monoCQAs is fully reversible. Through intramolecular acyl migration in monoCQAs, 5-CQA first isomerizes to 4-CQA (also known as cryptochlorogenic acid), then to 3-CQA (neochlorogenic acid), and finally to 1-CQA (Wianowska et al 2015b;Dawidowicz and Typek 2010;Xue et al 2016). It should be added that among the all 5-CQA isomers the presence of 3-and 4-CQA was confirmed in plants while the 1-CQA isomer is known only from theoretical considerations (Clifford 2000).…”
Section: Cqas Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Deshpande et al (2014) under the aqueous basic conditions the intramolecular acyl migration in monoCQAs is fully reversible. Through intramolecular acyl migration in monoCQAs, 5-CQA first isomerizes to 4-CQA (also known as cryptochlorogenic acid), then to 3-CQA (neochlorogenic acid), and finally to 1-CQA (Wianowska et al 2015b;Dawidowicz and Typek 2010;Xue et al 2016). It should be added that among the all 5-CQA isomers the presence of 3-and 4-CQA was confirmed in plants while the 1-CQA isomer is known only from theoretical considerations (Clifford 2000).…”
Section: Cqas Propertiesmentioning
confidence: 99%
“…Yet the monoCQAs are generally much more stable than the diCQAs under the same conditions. Taking into account the diCQAs stability, in Xue et al (2016) it was reported that 4,5-diCQa is much more stable than 3,4-diCQA and 3,5-diCQA. Citing the authors of this report, this might be due to the fact that diCQAs are more stable when the ester bond is attached to the quinic acid exists as an equatorial bond rather than the axial one.…”
Section: Cqas Propertiesmentioning
confidence: 99%
See 3 more Smart Citations